Mouse Magic - "Daniels, Lucy" (Hodder Childrens books: London, 1997)
Exciting animal stories for younger readers from Animal Ark, Lucy Daniels' best-selling series. Mandy is starring in the school play - and she plans to make her friend's mouse the star of the show!
Keywords: Mice as pets Juvenile fiction